Strategies of Sharia-Based Human Resource Management in the Implementation of an Islamic Curriculum at Happy Hive Playschool & Preschool Malaysia - Asmika, Fitri Dara; Amalia, Alfi (International Conference on Islamic Economic (ICIE), 2026)
The implementation of an Islamic curriculum in early childhood education institutions frequently encounters challenges related to inconsistent instructional practices caused by variations in teachers’ competencies, diverse educational backgrounds, and the suboptimal integration of Sharia values within the human resource management system. This condition reflects a gap between the design of the Islamic curriculum and its practical implementation in classroom settings. This study aims to analyze Sharia-based human resource management strategies, describe the implementation of the Islamic curriculum, and identify the role of HR management in supporting the consistency of curriculum implementation at Happy Hive Playschool & Preschool Malaysia. The study employed a descriptive qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and were analyzed interactively through data reduction, data display, and conclusion drawing. Triangulation techniques were applied to ensure data validity. The findings reveal that Sharia-based HR management strategies are implemented through character- and competency-based recruitment, continuous training and mentoring, and performance evaluation grounded in the principles of amanah (trustworthiness), ‘adl (justice), and ihsan (excellence). The Islamic curriculum is implemented through play-based learning, habituation of worship practices, and teachers’ role modeling. However, differences in teachers’ pedagogical and spiritual readiness continue to influence the equity of learning outcomes. This study affirms that the success of the Islamic curriculum is strongly determined by systematic and sustainable HR management integrated with the enhancement of teachers’ professional and spiritual competencies.